2021
DOI: 10.1002/nop2.1112
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' perceptions of their supportive role for cancer patients: A qualitative study

Abstract: Cancer is a debilitating and threatening disease and one of the global health problems with increasing prevalence (Zamanzadeh et al., 2013). A cancer diagnosis is an extremely unpleasant and unbelievable experience for individuals, and they often face a type of inner turmoil, identity conflict, isolation, anxiety, and depression, have difficulty in communicating with others (Monterosso et al., 2019), and need psychological and social-emotional support to increase self-confidence and a sense of peace (Nielsen e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…This scale includes 29 items divided into four objective subscales: interaction (items 1-5), performance (items 6-9), aesthetics (items 10-12), and information (items [13][14][15][16][17][18][19]. It also includes a subjective subscale measuring the program's subjective quality (items [20][21][22][23]. MARS also includes items intended to measure the program's perceived effectiveness for end users.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This scale includes 29 items divided into four objective subscales: interaction (items 1-5), performance (items 6-9), aesthetics (items 10-12), and information (items [13][14][15][16][17][18][19]. It also includes a subjective subscale measuring the program's subjective quality (items [20][21][22][23]. MARS also includes items intended to measure the program's perceived effectiveness for end users.…”
Section: Methodsmentioning
confidence: 99%
“…Along with other dimensions, the social health dimension is equally critical in bringing a person to balance and integration, and the role of social care is one of the basic duties of nurses [21]. Nurses can use various communication strategies to provide holistic, quality, and humane care to different patient groups [22,23]. Digital health technology is a new communication solution that has attracted the interest of patients and related service providers in recent years to access cancer care services [24].…”
Section: Introductionmentioning
confidence: 99%
“…The scope and standards of oncology nursing practice prepare nurses to collect in-depth data regarding the “physical, psychosocial, social, spiritual, and cultural health status of patients [ 12 ]; therefore, oncology nurses are expected to be able to identify emotional distress and to plan and provide nursing care that meets each patient’s individual needs [ 13 ]. From some oncology nurses' perspectives, providing cancer patients with psychological support are including caring compassionately with emotional support, having a friendly relationship with the patient and having communicative behavior facing patient needs [ 14 ]. Unfortunately, previous research found that most healthcare professionals (HCPs), including nurses, find it difficulty, and frequently fail to recognize such symptoms among patients [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nurses play an "indispensable role in the care" of children with cancer, 12 providing a "canopy for cancer patients" that shelters them from the sequelae of their disease. 13 Inpatient nurses often take a primary role in symptom management, serving as the first point of contact for helping children and their families feel comfortable during hospitalizations. 14 They are highly effective at helping pediatric oncology patients cope with their medical experience.…”
Section: Introductionmentioning
confidence: 99%
“…Although prior studies have focused on the patient/family and oncologist, one notably overlooked group in this research is nurses. Nurses play an “indispensable role in the care” of children with cancer, 12 providing a “canopy for cancer patients” that shelters them from the sequelae of their disease 13 . Inpatient nurses often take a primary role in symptom management, serving as the first point of contact for helping children and their families feel comfortable during hospitalizations 14 .…”
Section: Introductionmentioning
confidence: 99%